Enhance MySejahtera to study Long Covid - Ahmad Mahfuz, Gazali (CodeBlue.org, 2021)
My uncle and I were travelling together for a few days at the end of November this year. Several days after parting ways with him, I developed flu-like symptoms such as fever, cough, sore throat and others that seem like COVID-19. The symptoms seemed to worsen, so I decided to go to a clinic to perform the COVID-19 test.